Nurturing the Teaching Soul: An Investigation on How Participation in Online Communities and Social Networks Boosts Academics Well-being, Professional Satisfaction, and Resilience - Uzorka, Afam; Kalabuki, Kagezi (Social Education Research, 2024)
This study explores how online community and social network participation impact academics' well-being, professional satisfaction, and resilience. It aims to provide insights into the role of digital platforms in nurturing the teaching soul, a concept encompassing academics' intrinsic motivation, passion, and emotional commitment to their profession. Utilizing a qualitative approach, the research involved interviews with 13 administrators and 43 lecturers from 10 Ugandan universities, totalling 56 participants. The study employed a semi-structured interview guide developed based on social constructivism, focusing on online interactions' collaborative and supportive nature. Data were analyzed using NVivo 12 through thematic coding, with themes developed iteratively to ensure mutual exclusivity and address potential overlaps. The study identified three main themes: Supportive online communities, professional growth and satisfaction, and resilience building. The findings highlight the positive impact of online communities on various aspects of academics' professional lives. The study contributes to understanding how digital platforms can be harnessed to support and enhance academics' well-being, satisfaction, and resilience. Future research should explore longitudinal impacts and the effectiveness of specific online community practices. Practical recommendations include developing targeted university policies to leverage online communities for professional development and well-being initiatives, ensuring that these digital tools are effectively integrated into academics' professional lives.